FOOD-RELATED IDIOMS IN ENGLISH: A CULTURAL AND LINGUISTIC PERSPECTIVE - Kamolova Rushana Ibodovna; Yusupova Shoira Botirovna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation:  This  article  targets  at  exploring  the  most  common  food-related idioms in the English language, analyze their figurative meanings and cultural origins, and discuss their equivalents in Uzbek. Moreover, it addresses the importance of these idioms in language learning and cross-cultural communication.